Warranty Optimization in a Dynamic Environment. (15th April 2009) - Dimitrov, Nedialko B.; Chukova, Stefanka
Abstract : A product warranty is an agreement offered by a producer to a consumer to replace or repair a faulty item, or to partially or fully reimburse the consumer in the event of a failure. Warranties are very widespread and serve many purposes, including protection for producer, seller, and consumer. They are used as signals of quality and as elements of marketing strategies. In this study we review the notion of an online convex optimization algorithm and its variations, and apply it in warranty context. We introduce a class of profit functions, which are functions of warranty, and use it to formulate the problem of maximizing the company's profit over time as an online convex optimization problem. We use this formulation to present an approach to setting the warranty based on an online algorithm with low regret. Under a dynamic environment, this algorithm provides a warranty strategy for the company that maximises its profit over time.